The Effect of the Use of Serial Image Media on Elementary School Students' Narrative Essay Writing - Nurma Dayanti; Riris Nurkholidah Rambe (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Narrative writing skills are one of the language skills that are very important for students to master in elementary school. However, there are still many students who have difficulty developing ideas, arranging storylines in a logical order, and applying the right structure and language rules in their narrative writing. This problem is largely due to the lack of use of learning media that can provide visual stimulation and help students understand the sequence of events more realistically. This study aims to identify the impact of the use of serial picture media on the narrative writing skills of grade V students of SDN 050635 Tanjung Nguda. This study uses a quantitative approach with quasi-experimental methods and nonequivalent control group design. The research sample amounted to 42 students consisting of 21 experimental class students and 21 control class students. Data collection techniques were carried out through narrative writing tests, observations, and documentation. Data analysis was carried out using descriptive statistics, N-Gain analysis, normality test, homogeneity test, Independent Sample T-Test and Cohen's d analysis. The results showed that the average posttest score in the experimental group was 81.67, which was higher than the control group that obtained an average of 62.62. The results of the hypothesis test indicated a significance value of 0.000 < 0.05 so that H₀ was rejected andHₐ was accepted. In addition, the results of Cohen's d analysis of 1.36 showed a large effect size, so the use of serial picture media had a strong influence on students' narrative writing skills. Thus, serial picture media has been proven to have a significant effect on the narrative essay writing skills of elementary school students.